2006
DOI: 10.1002/polb.20829
|View full text |Cite
|
Sign up to set email alerts
|

Structural arrangement of crystalline/amorphous phases of polyethylene‐block‐polystyrene copolymer as induced by orientation techniques

Abstract: ABSTRACT.Polyethylene-block-polystyrene (PE-block-PS) copolymer film having bicontinuous crystalline/amorphous phases were tensile-drawn under various conditions for structural arrangement of these phases. When a draw was made below melting temperature of PE crystalline phase (95 o C), the bicontinuous structure was gradually destroyed with increasing strain, due to the lower ductility of PS having glass-transition temperature around 100 o C. Correspondingly, the necking phenomenon was clearly recognizable dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Solid‐state relaxation after drawing of UHMW‐PE also enables a control of molecular rearrangement, resulting in a periodic arrangement composed of lamellar crystals and amorphous layers 14. Such ordered‐phase morphology is quite similar to microphase separation of block copolymers 15–21. Here, the former lamellar thickness of 30 nm coincides with the segmental length corresponding to the critical MW between entanglements (3600 Da) for PE,22 which play a role similar to that of molecular linking points of the block copolymer chain, in terms of the boundary determining the phase separation ( Figure ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Solid‐state relaxation after drawing of UHMW‐PE also enables a control of molecular rearrangement, resulting in a periodic arrangement composed of lamellar crystals and amorphous layers 14. Such ordered‐phase morphology is quite similar to microphase separation of block copolymers 15–21. Here, the former lamellar thickness of 30 nm coincides with the segmental length corresponding to the critical MW between entanglements (3600 Da) for PE,22 which play a role similar to that of molecular linking points of the block copolymer chain, in terms of the boundary determining the phase separation ( Figure ).…”
Section: Introductionmentioning
confidence: 91%
“…Here, it should be noted that characteristic morphologies of block copolymer are available for the preparation of functional materials. We have obtained bicontinuous networks of microphase separation for diblock copolymers containing both crystalline and amorphous segments by varying the crystallization conditions 17, 18, 21. Further selective sulfonation or etching of amorphous components gave a electrolyte or nanoporous membrane supported by the surviving counter crystalline PE network.…”
Section: Introductionmentioning
confidence: 99%
“…The base copolymer is the same material used in our previous studies. 26,27,29,31 The chemical agents used for preparing the nanoporous membranes were p-xylene (98% purity) and fuming nitric acid (FNA) (97% purity) supplied from Wako Chemical in Japan. The D-glucose and bovine serum albumin (BSA) solutions for permeation tests were purchased from Aldrich in the USA.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, diblock copolymer composed of polyethylene (PE) and polystyrene (PS), PE-b-PS, exhibits the desirable bicontinuous crystalline/amorphous phase separation when it is crystallized under optimum conditions. 26,27 Selectively removing the amorphous phase of both PE and PS components through acid etching treatment yielded a characteristic network morphology of nanopores passing through the membrane thickness. The residual crystalline PE networks are the supporting component for this nanoporous membrane, thus it is robust and exible.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the deconvolution analysis of DSC profiles is useful for evaluating the constitution of crystalline domains in the bicontinuous crystalline/amorphous structure of isothermally crystallized PE-b-PS. KEY WORDS Polyethylene /Polystyrene Block Copolymer / Isothermal Crystallization / Melting / DSC Measurement / Deconvolution Analysis / (Received September 6, 2018: Accepted November 5, 2018: Advance Publication December 18,2018) [ Kobunshi Ronbunshu, 76, 150-156 (2019)] ©2019, The Society of Polymer Science, Japan…”
mentioning
confidence: 99%